Development of West Nile virus candidate vaccines in Nicotiana benthamiana - Wayland, Jennifer (Department of Molecular and Cell Biology, 2022)
West Nile virus (WNV) is a widely disseminated flavivirus, with a geographical range that now includes Africa, America, Europe, the Middle East, West Asia and Australia. The virus is vectored by Culex mosquitoes and is maintained in a bird-mosquito transmission cycle with hundreds of bird species acting as reservoir hosts. In humans, infections can develop into febrile illness and severe meningoencephalitis and to date, there is no treatment or vaccine available. In horses, approximately 20% of infections are symptomatic, of which 90% of cases involve neurological disease, with 30-40% fatality rates. Several veterinary vaccines specific to the lineage 1 WNV strains are commercially produced in America and Europe, however, these vaccines are not easily obtainable for low and middle-income countries (LMIC) due to their high cost and that associated with importation as well as the need for annual vaccination. Due to continuous global disease outbreaks in birds, humans and horse populations with no preventative measures for humans, WNV poses a major public health threat, especially in naïve populations. The development of a vaccine that contributes to the ‘One Health' Initiative could be the answer to prevent the spread of the virus and control the disease. Current veterinary vaccines are produced in expensive cell culture systems that require sterile conditions, high-level biosafety facilities and trained personnel for their preparation. Transient plant-based expression systems have proven to be a very cost-effective means of making complex proteins. Plants can produce and modify proteins in a similar manner to mammalian cells and production does not require sterile conditions or specialised facilities. We propose that plants could be a viable means of making feasible, low-cost reagents for WNV, specifically virus-like particles (VLPs) for use as vaccines in South Africa and other LMIC. In this study, we set out to develop two particulate candidate vaccines based on a virulent South African WNV strain using Nicotiana benthamiana as the expression platform. We aimed to develop the first candidate vaccine by exploiting the virus's ability to form noninfectious VLPs by expressing only the WNV membrane (prM – precursor, M – matured) and envelope (E) proteins. Infiltration of these recombinant plasmids into plants yielded no protein expression unless co-expressed with the human chaperone protein calnexin (CNX), upon which expression of both M and E proteins were observed. We investigated the assembly of prM and E into VLPs by transmission electron microscopy (TEM), however, purification of these particles proved difficult with poor reproducibility and VLP yield. This led to the development of an alternative candidate vaccine making use of the antigendisplay technology based on the SpyTag (ST) and SpyCatcher (SC) peptides. The immunodominant epitope of the WNV E protein, domain III (EdIII), was selected for antigen display. Two constructs of the EdIII gene were generated, one with the SC peptide on the 5'- (SC-EdIII) and the other on the 3' end (EdIII-SC). Both SC-EdIII and EdIII-SC proteins were successfully expressed in the presence of the human chaperone protein calreticulin, and purified with yields of 9 mg/kg and 69 mg/kg fresh leaf weight (FLW), respectively. The VLP core selected for the display of the SC-linked EdIII proteins comprised the coat protein of the bacteriophage AP205 with the ST peptide linked to its N-terminus (ST-AP205). Spytagged-VLPs were purified by density gradient ultracentrifugation at a yield of approximately 50 mg/kg FLW. The purified SC-linked EdIII proteins and ST-AP205 VLPs were coupled in vitro, but successful complex formation of AP205:EdIII was only observed between ST-AP205 and EdIII-SC and not when the SC peptide was located on the N-terminus of EdIII. We further demonstrated the successful complex formation of AP205:EdIII in vivo by coinfiltration of the EdIII-SC and ST-AP205 constructs, as well as by extracting leaves of plants infiltrated individually with either of the constructs. Due to the ease of purification and the high yields of AP205:EdIII achieved, the co-extraction process was optimised to obtain the best coupling yield possible by evaluating different FLW extraction ratios and the formation of VLPs was confirmed by TEM. The optimal co-extraction process was established at a FLW ratio of 1:2 ST-AP205 to EdIII-SC yielding approximately 23 mg/kg AP205:EdIII/FLW processed. In this study, we describe the successful production of two particulate candidate vaccines. The first is based on the expression of the WNV prM and E genes in the presence of human CNX and the second is based on the ST/SC antigen-display technology. These outcomes exhibit the potential plants have of being used as biofactories for making significant pharmaceutical products for the ‘One Health' Initiative and could be used to address the need for their local production in LMIC.